DILEMA TRADISI DAN MODERNITAS TELAAH ATAS “KRITIK NALAR ARAB” MUHAMMAD ABID AL-JABIRI - Izzuddin Washil (The Pontianak State Institute of Islamic Studies, 2013)
Al-Jabiri denominated his interpretation project of the Arabic tradition as the Arabic reasoning critique (naqd al-aql al-arabi). The project began from his concern over the present reality of the Arab and Islamic world which arguably is still underdeveloped and his desire to present a new thought methodology as a tool to get out of the slump and awaken to the preferred reality. Al-Jabiri differentiated two traditions, one that refers to the tadwin of Islam as part of Islamic-Arabic tradition and the other referring to and departing from the European Renaissance (modernity). The gap between